Analisis Hubungan Kecemasan Terhadap Produksi Asi Pada Ibu Postpartum: Literature Review - Wafa Wafiah Purnamawati; Ariani Fatmawati; Bhekti Imansari (Jurnal Keperawatan Muhammadiyah, 2022)
Background: Anxiety is a psychological disorder that often occurs in postpartum. Anxiety experienced by postpartum mothers will have an impact on milk production. The purpose of this study was to analyze the relationship between anxiety and milk production in postpartum. Method: This study used scientific articles with literature review methods and designs with database searches carried out from March to April 2021 through Pubmed, Science Direct, Sage, Google Scholar and ProQuest with the keyword of “Anxiety” OR  “Anxiety disorder” OR “Stress” AND ”Breast Milk” OR “Breast output” OR “Breast feeding” OR “Milk Production” AND ”Postpartum” OR “Postnatal” and "Hubungan kecemasan dan produksi ASI ibu postpartum” (2016-2021). Results: From the 75 articles there were 10 articles it shows that there are several influencing factors  primiparous, breastfeeding, low birth weight, fatigue due to childbirth and age, education and work factors.Conclusion: This study shows that anxiety has a significant relationship to the smoothness of breastfeeding in postpartum. Suggest:The suggest can be given that the health workers increase outreach activities regarding the importance of choosing appropriate coping strategies to reduce maternal anxiety levels that can affect breast milk production.